Prosthetic management of mid-facial defect with magnet-retained silicone prosthesis - Buzayan, M.M. (2013)
BACKGROUND AND AIM: Mid-facial defect is one of the most disfiguring and impairing defects. A design of prosthesis that is aesthetic and stable can be precious to a patient who has lost part of his face due to surgical excision. Prosthesis can restore the patients' self-esteem and confidence, which affects the patients and their life style. The aim of this case report is to describe a technique of mid-facial silicone prosthesis fabrication. TECHNIQUE: To provide an aesthetic and stable facial prosthesis, the extra-oral prosthesis was fabricated using silicone material, while the intra-oral defect was restored with obturator prosthesis, and then both prostheses were connected and attached to each other using magnets. DISCUSSION: This clinical report describes the rehabilitation of a large mid-facial defect with a two-piece prosthesis. The silicone facial prosthesis was made hollow and lighter by using an acrylic framework. Two acrylic channels were included within the facial prosthesis to provide the patient with clean and patent airways. CLINICAL RELEVANCE: A sectional mid-facial prosthesis was made and retained in place by using magnets, which resulted in a significant improvement in the aesthetical and functional outcome without the need for plastic surgery. Silicone prostheses are reliable alternatives to surgery and should be considered in selected cases.